Fetal intra-abdominal umbilical vein varix - Correia,Ana Isabel (2018)
Fetal umbilical intra-abdominal vein varix is a rare congenital malformation characterized by focal dilatation of the umbilical vein. It's clinical significance is unclear and is usually an isolated finding, in some cases it may be associated with other fetal anomalies, chromosomal defects or fetal death. The authors report a case of pregnant woman at 25 weeks of gestation with a fetus affected by dilatation of an intraabdominal portion of the umbilical vein, with a favorable progress and outcome.